Lentivirus-Mediated Nox4 shRNA Invasion and Angiogenesis and Enhances Radiosensitivity in Human Glioblastoma - Li, Yongsheng (Hindawi Publishing Corporation, 2014)
Radioresistance remains a significant therapeutic obstacle in glioblastoma. Reactive oxygen species (ROS) are associated with multiple cellular functions such as cell proliferation and apoptosis. Nox4 NADPH oxidase is abundantly expressed and has proven to be a major source of ROS production in glioblastoma. Here we investigated the effects of Nox4 on GBM tumor cell invasion, angiogenesis, and radiosensitivity. A lentiviral shRNA vector was utilized to stably knockdown Nox4 in U87MG and U251 glioblastoma cells. ROS production was measured by flow cytometry using the fluorescent probe DCFH-DA. Radiosensitivity was evaluated by clonogenic assay and survival curve was generated. Cell proliferation activity was assessed by a cell counting proliferation assay and invasion/migration potential by Matrigel invasion assay. Tube-like structure formation assay was used to evaluate angiogenesis ability in vitro and VEGF expression was assessed by MTT assay. Nox4 knockdown reduced ROS production significantly and suppressed glioblastoma cells proliferation and invasion and tumor associated angiogenesis and increased their radiosensitivity in vitro. Our results indicate that Nox4 may play a crucial role in tumor invasion, angiogenesis, and radioresistance in glioblastoma. Inhibition of Nox4 by lentivirus-mediated shRNA could be a strategy to overcome radioresistance and then improve its therapeutic efficacy for glioblastoma.